The Importance of Definitive Diagnosis in Chronic Schistosomiasis, with Reference to Schistosoma haematobium - Clive Shiff (Journal of Parasitology Research)
Schistosomes are long-lived parasites, hence schistosomiasis is a chronic disease with severe long-term implications. However, definitive diagnosis of active infection has been difficult because demonstration of infection has depended on detecting parasite eggs in urine and/or stool. In the case of Schistosoma haematobium which parasitizes the urinogenital system, this method has low sensitivity in adults. Detection of parasite-specific DNA in urine has been demonstrated and this has similar specificity but improved sensitivity. The implications of this new procedure and the impact on diagnosis are discussed.